Identification and molecular characterization of cotton leaf curl Gezira betasatellite and two distinct begomoviruses infecting papaya trees in the Kingdom of Saudi Arabia: Genetic diversity of begomoviruses infecting Papaya - Hussain, Khadim; Khalid, Zaheer; Amer, Mahmoud A; Zaman, Muhammad; Amir, Muhammad; Al-Shahwan, Ibrahim M; Zakri, Adel M; Al-Saleh, Mohammed A (Cellular and Molecular Biology, 2022)
Begomovirus is the largest genus in the family Geminiviridae and constitutes more than 445 virus species. Begomoviruses are characterized by single-stranded circular genomes with monopartite or bipartite components and transmitted by whitefly (Bemisia tabaci). Begomoviruses cause severe diseases in many economically important crops throughout the world. Typical symptoms of a begomovirus infection including severe leaf curling, vein thickening, vein darkening and reduced leaf size were observed in papaya plants in the Dammam district of the Eastern Province of Saudi Arabia during the growing season in 2022. A total of 10 samples were collected, and total genomic DNA was isolated from naturally infected papaya tree samples and subjected to PCR amplification using universal diagnostic primers for begomoviruses and associated satellites. Three PCR-amplified genomic components of begomoviruses and betasatellite namely P61Begomo (645 bp), P62Begomo (341 bp) and P62Beta (563 bp) were sent for Sanger DNA sequencing to Macrogen Inc. These partial viral genome sequences were submitted to Genbank database and accession numbers ON206051, ON206052 and ON206050 were assigned to P61Begomo, P62Begomo and P62Beta respectively. Phylogenetic analysis and pairwise nucleotide sequence identity studies identified P61Begomo was identified as Tomato yellow leaf curl virus, P62Begomo as DNA A component of a bipartite begomovirus Watermelon chlorotic stunt virus and P62Beta as begomovirus associated betasatellite; Cotton leaf curl Gezira betasatellite. To the best of our knowledge, this is the first report of a begomovirus complex infecting papaya (Carica papaya) in the Kingdom of Saudi Arabia.